2020
DOI: 10.20408/jti.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Contusion Similar to COVID-19 Pneumonia

Abstract: The Coronavirus disease 2019 (COVID-19) has rapidly spread across the world and caused a pandemic. It can be transmitted by an infected person or an asymptomatic carrier and is a highly contagious disease. Prevention and early identification of COVID-19 are important to minimize the transmission of COVID-19. Chest computed tomography (CT) has a high sensitivity for detecting COVID-19, but relatively low specificity. Therefore, chest CT may be difficult to distinguish COVID-19 findings from those of other infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Six of these surveys were case reports that exclusively showed some similarities, although they did not conduct proper criteria to differentiate these two entities. 19 , 20 , 21 , 22 , 23 , 24 Five out of six case reports had pulmonary contusions, and their CT images showed bilateral multifocal lesions. Based on our results, we concluded that the prevalence of bilateral lung involvement is higher in pure pulmonary contusion, although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these surveys were case reports that exclusively showed some similarities, although they did not conduct proper criteria to differentiate these two entities. 19 , 20 , 21 , 22 , 23 , 24 Five out of six case reports had pulmonary contusions, and their CT images showed bilateral multifocal lesions. Based on our results, we concluded that the prevalence of bilateral lung involvement is higher in pure pulmonary contusion, although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%